Accountability, transparency, Participation, and Inclusion. A New Deve lopment Consensus? - Carothers, Thomas; Brechenmacher, Saskia (Carnegie Endowment for International Peace, 2014)
The wide-reaching consensus around the normative and instrumental valu e of accountability, transparency, participation, and inclusion remain s less solid than enthusiasts of these concepts might wish.